Towards the Creation of an Adequate Legal Regime for the Active Space Debris Removal from Outer Space - Ivan A. Kosenkov; Irina Yu. Shtodina (Московский журнал международного права)
The article deals with the problem of development of an adequate legal regime for the active space debris removal from outer space. Authors examine the existing norms of international space law through the prism of their applicability to the active space debris removal issue. The authors attempt to offer the international legal regime for space debris, encouraging space activities participants to actively remove it. The article also concerns the regulatory aspects of monitoring of outer space, liability for damage caused by space debris removal operations, giving suggestions regarding the organizational aspects of such activities.